ISLAMISASI ILMU PENGETAHUAN Studi Kritis Pemikiran Syed Muhammad Naquib Al-Attas - rofiq kurniawan (STIT AL-ISHLAH BONDOWOSO, 2018)
Naquib Al-Attas is one of the thinkers of Islamic education who can also master other fields of science, he is the figure who formulated the idea of ​​Islamization of science in the form of an educational curriculum. The ideas of Islamization of science that he offers, emphasizes its own approach and methodology while still being based on the normative legitimacy of the Qur'an and Hadith. In addition, he also proposed that the most appropriate term of Islamic education is ta'dib and not the term tarbiyah or ta'lim as agreed by the majority of Muslim scholars in the world, this opinion cannot be taken lightly even though it should not be accepted without reservation. The idea of ​​Naquib Al-Attas, as mentioned, has shown the reformulation of the face of Islamic education as an integrated and intact education system. This can be seen from the educational goal of realizing the individual Insan Kamil. Based on the description that the author has described above, it can be concluded: first; According to Al-Attas, the term discipline is more appropriate for the term Islamic education, not education and education. Second; The concept of sneezing renewal for Islamic education lies in the system and its goals. Third. Al-Attas is classified in the map of Islamic education reform as a reform aimed at pure Islam with reference to the Qur'an and hadith. Keywords: Islamization of science, tarbiyah, ta'lim, ta'dib